Multidisciplinary clinical approach by sharing oral examination information to treat a diabetes patient with dysgeusia. Issue 5 (22nd March 2019) - Matsunaga, Kazuyuki; Yoshida, Yasuko; Takemaru, Makoto; Yamashiro, Keisuke; Monden, Ikuko; Inohara, Ken; Nakagawa, Saki; Maeda, Eriko; Nakahama, Kanako; Kohriyama, Tatsuo; Takashiba, Shogo
Key Clinical Message: Taste alteration is one of the complications of severe diabetes. It is important in diabetes treatment to assess taste alteration and perform dietary counseling, therapeutic exercise, and oral care. In this case, multidisciplinary clinical approach by medical staff was successful for a severely diabetic patient with dysgeusia. Abstract : Taste alteration is one of the complications of severe diabetes. It is important in diabetes treatment to assess taste alteration and perform dietary counseling, therapeutic exercise, and oral care. In this case, multidisciplinary clinical approach by medical staff was successful for a severely diabetic patient with dysgeusia.